Effects of adding multiwall carbon nanotubes on performance of polyvinyl acetate and urea-formaldehyde adhesives in tropical timber species - Rodríguez-Zúñiga, Ana (2015)
https://www.scopus.com/inward/record.url?eid=2-s2.0-84940754701&partnerID=40&md5=1821f371fbf5ca780f855a8c5c875e01